Μελέτη του ανιχνευτή Microbulk Micromegas με διαμέριση του μικροπλέγματος με χρήση της κάρτας Feminos - Γιακουμογιαννάκη, Χαριδήμη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2018)
The main subject of this thesis is the the performance of a real x-y microbulk Micromegas with a segmented micromesh. The segmented mesh microbulk was an I.N.P.P. Demokritos initiative along with IRFU Sacley, CERN and University of Saragossa, realized through RD51 Collaboration funding, aiming to design and built a microbulk Micromegas with a x-y readout structure, albeit with signifcantly simplifed topology: the y strips are located on the mesh grid instead of under the anode x-strip layer as it is typically done. O microbulk of that sort maintains the excellent energy resolution of a typical microbulk while improving on its radiopurity with a backround detection capability of the order of 10-7cnts/keV/cm2/sec ,to wit improved by one order of magnitude. High radiopurity and minimalistic design render the segmented mesh microbulk suitable candidate for rare events low threshold searches. The first part of the experiments includes detector characterization in the context of an aging study three years after its construction and first use. This is done with the employment of a multichannel analyzer and a standard Nuclear Instrumental Module as part of the experimental set up. The second part entails the use of a special readout card, the Feminos, for the utilization of the detector in semi TPC mode and reconstruction of particle trajectories in two dimensions.